Indigenous Knowledge Systems of Solid Waste Management in Bushbuckridge Rural Communities, South Africa - Benett Siyabonga Madonsela; Machete Machete; Karabo Shale (Waste)
Indigenous knowledge systems related to solid waste management in economically marginalized communities have been largely overlooked in the scientific literature, even though the indigenous communities of developing nations struggling to manage solid waste rely on these practices. It is startling that indigenous solid waste management practices are scarcely documented in the scientific literature despite their position as potential alternative disposal methods. This gap persists amid limited municipal budgets, inadequate waste collection services, and poor infrastructure in economically marginalized indigenous rural communities in developing nations. Subsequently, in the discipline of solid waste management, this obstacle impedes the recognition and inclusion of indigenous waste management practices into integrated waste management plans. As a result, this causes a delay in their progress or elevation to the same level of credibility as mainstream scientific knowledge. In the process, this relegates the waste management practices of indigenous communities to the background. Against this background, the current study sought to investigate the indigenous solid waste management practices of rural communities in Bushbuckridge Local Municipality. As such, ten cases that captured the spatial cultural diversity of indigenous communities’ practices across Bushbuckridge Local Municipality (BLM) were selected for sampling. Data were collected using ethnographic research methods. Data analysis was carried out using the thematic analysis approach. Inductive logic was used in the interpretation of the current study results. The results of the current study indicate that indigenous communities of Bushbuckridge Local Municipality, in the absence of formal waste management services from the local authority, resort to an indigenous knowledge system to manage solid waste. Waste burning (100%), open-air dumping (100%), and backyard pits (90%) are some of the indigenous waste management practices espoused by the rural communities of BLM. The similarity in practices was corroborated by statistical inferences that revealed that between BLM communities, the amount of indigenous waste management practices is not significant (p > 0.05). However, there are concerns that despite the sustainability aspect associated with recycling (<25%) practices, these disposal methods are not common in the rural communities of BLM. This is a setback for an indigenous knowledge system that is supposed to advance environmental sustainability practices.